Open science cannot succeed without open peer review - Tsakonas, Giannis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Open Science principles have been a critical driver for change in scholarly communication. Opening up research publications has led to encouraging rates of growth of Open Access but it has now become evident that true and system-wide change will only come if all the publishing components are open, including those at the production stages. We are seeing a growing demand to know more about how research papers qualify for publication and if we wish to engender more trust in scholarly outputs – trust within the scholarly communication community and trust of the wider public – we should listen carefully and seek to act on these demands. However, when an entire system has been fixed in its ways for many years, it is not easy to shake things up. In short, while it may be reasonable to ask for changes, not all of these will be welcomed or be embraced. Peer review is one of these publishing components. Regardless of the types and forms in each publication venue, it supposedly ensures that the intellectual work of an author has been checked, improved and qualified for publication after constructive dialogue among all participants; the author, the editor and the reviewers. We recognise it as an important process that validates the quality of a publication, which can be trusted by the reader and – as trusted – will be used in solving research problems and sometimes underpin changes in public policy. While the principles of peer review are still valid, in an Open Science system the current closed and entirely opaque operation of this system seems obsolete and even vicious. Masked by anonymisation and based on linearity this very regulated dialogue serves largely the prestige of publishing venues and individuals. Changes are needed, but we should acknowledge beforehand that changing peer review is a challenging exercise. The issues around peer review are complex, requiring alternative management of both the processes and the actors.